Galectin-1 functions as a Th2 cytokine that selectively induces Th1 apoptosis and promotes Th2 function - Motran, Claudia Cristina (2008)
Galectin-1 has been implicated in regulating T-cell survival, function, and Th1/Th2 balance in several mouse models, though the molecular and cellular basis of its immunomodulatory activity has not been completely elucidated. Therefore, we examined galectin-1 expression and activity within differentiated murine Th1 and Th2 subsets. While recombinant galectin-1 specifically bound to both T-cell subsets, Th1 and Th2 T cells expressed distinct combinations of galectin-1-reactive epitopes and were differentially responsive to galectin-1 exposure. Indeed, Th1 cells were more susceptible to galectin-1-induced death than Th2 cells. Th2 protection from apoptosis was correlated with expression of anti-apoptotic galectin-3. Further, galectin-1 promoted TCR-induced type 2 cytokine production by Th2 cells. Differentiated Th2 cells constitutively expressed high levels of galectin-1 and can be induced to produce even higher levels of galectin-1 with restimulation, whereas comparable levels of galectin-1 in Th1 cells were only observed after restimulation. Co-culturing experiments using galectin-1/ and galectin-11/1 Th1 and Th2 T cells demonstrated that Th2-derived galectin-1 induced Th1 apoptosis, whereas Th1-derived galectin-1 promoted Th2 cytokine production. These studies identify galectin-1 as a cross-regulatory cytokine that selectively antagonizes Th1 survival, while promoting TCR-induced Th2 cytokine production